Dermatologist in Orthopedic Ward: Prevalence and Pattern of Dermatological Complications of Orthopedic Implants and Procedures – An Observational Study in 100 Cases (Journal of Pakistan Orthopaedic Association, 2025)
Objective: This study was done to assess the prevalence and pattern of various dermatological manifestations and their contributing factors after orthopedic surgical interventions.Methodology: Prospective observational study was done at Dermatology department, Services Hospital Lahore for 6 months after taking ethical approval. 100 cases were included by non-probability consecutive sampling. Post-operative admitted patients in orthopedic ward having some skin complications were included after taking their consent. Patients having any dermatosis before surgery, incomplete clinical/surgical data were excluded. Demographic data was noted, type of procedure done, type of skin complication observed, duration of lesion, contributing or comorbid factors were recorded in predesigned proforma. Diagnosis where needed was confirmed by skin smears or histopathology. Data was analyzed in SPSS version 27; means were calculated for quantitative variables and frequency percentages for qualitative variables.Results: Significant incidence of conditions ranging from contact dermatitis and surgical site infections to rare complications like metal hypersensitivity and prosthesis abscess were noted.Conclusion: Complications due to orthopedic treatments were seen in 53% cases. Dermatologist plays a vibrant role in early diagnosing and managing infections and other eczematous reactions seen after orthopedic interventions.